PENGARUH HABITAT MANGROVE TERHADAP PENURUNAN TINGKAT CEMARAN TIMBAL DI MUARA SUNGAI TALLO - Novita Pangruruk; Subari Yanto; Patang Patang (Universitas Negeri Makassar, 2022)
This study aims to determine the effect of mangrove habitat on the level of lead (Pb) contamination and its effect on the quality of water, soil and fish in the waters of the Tallo River estuary. This research is a descriptive type of research using survey methods. This research was carried out by taking samples of water, fish, soil at three stations namely, Station I Mangrove Forest area, Station 2 Tallo River Estuary and Station 3 Port of Paotere. The results of this study indicate that lead (Pb) pollution along the waters of the Tallo River, has exceeded the water threshold of 0.01725 mg /l, fish 0.05615 mg/kg and land as much as 36.113 mg/L according to Rangkuti (2009). In addition, from the linear regression test it was found that lead had a significant effect (F> 0.05) on pH and salinity. However, lead has no significant effect (F <0.05) on temperature, dissolved oxygen, ammonia, nitrite and plankton.